A design study for a compound helicopter featured with a convertible prop/rotor - Mostafa, A. (Cranfield University, 1989)
A compound helicopter is a hybrid vehicle, fundamentally a helicopter. It uses an auxiliary lift and propulsion device(s) in order to eliminate the lifting rotor high speed limitation of retreating blade stall effects, thus allowing flight characteristics comparable in many respects to those of fixed-wing aircraft. The primary objective of this thesis was to perform a design study investigating the validity of the concept of compounding, then selecting and designing a shaft-driven single compound helicopter intended for use as a ground support and anti-tank VTOL aircraft. The selection included a complete parametric and sizing analysis which were based on three defined maj or mission requirements: a maximum forward speed of 250 knots; payload of 1500 lb and cruising endurance of 3 hours at 225 knots. Of the many configurations studied, a single-rotor compound helicopter featured with convertible tail prop/rotor was found to be the most suitable for the intended application. Stability/control characteristics and performance capability of the designed aircraft were found to meet or exceed military specifications and flying quality requirements. structure, dynamics and cost analysis were considered to be beyond the scope of the design study.